Dealing with hazardous spills - Smith, Bo; Luttrell, Stephen; SafetMax Corp. Pte. Ltd. ([singapore] : SafetMax Corp. Pte. Ltd.)
This program explains the safety measures in deals with hazardous spills, includes preparing the emergency response plan. this program also suggest five training level of safety measure and also tips for acting on situation
Title from title screen
Executive producer, Donald L. Leonard ; editor, J.W. Pukatsch
Keywords: Hazardous substances -- Safety measures; Hazardous substances -- Accidents